1998
DOI: 10.1128/mcb.18.2.953
|View full text |Cite
|
Sign up to set email alerts
|

Viral Repression of Fungal Pheromone Precursor Gene Expression

Abstract: Biological control of chestnut blight caused by the filamentous ascomycete Cryphonectria parasitica can be achieved with a virus that infects this fungus. This hypovirus causes a perturbation of fungal development that results in low virulence (hypovirulence), poor asexual sporulation, and female infertility without affecting fungal growth in culture. At the molecular level, the virus is known to affect the transcription of a number of fungal genes. Two of these genes, Vir1 and Vir2, produce abundant transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 31 publications
2
87
1
2
Order By: Relevance
“…Any shift in the balance of resources that increases C. parasitica asexual sporulation rate would then benefit CHV1. For instance, the sexual castration that has been reported in some hypovirulent C. parasitica isolates (Zhang, Baasiri, & Van Alfen, 1998) could be interpreted as redirection of resources away from traits not benefiting viral fitness. The observation of a positive relationship between somatic growth and asexual reproduction in hypovirulent isolates could then suggest that CHV1 when infecting C. parasitica releases in its host a constraint between two important life‐history traits—that we found to be negatively correlated in uninfected isolates—in order to benefit to its own fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Any shift in the balance of resources that increases C. parasitica asexual sporulation rate would then benefit CHV1. For instance, the sexual castration that has been reported in some hypovirulent C. parasitica isolates (Zhang, Baasiri, & Van Alfen, 1998) could be interpreted as redirection of resources away from traits not benefiting viral fitness. The observation of a positive relationship between somatic growth and asexual reproduction in hypovirulent isolates could then suggest that CHV1 when infecting C. parasitica releases in its host a constraint between two important life‐history traits—that we found to be negatively correlated in uninfected isolates—in order to benefit to its own fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Species of the Ascomycetes for which putative prenylated precursors have been reported in the literature include the following: the fission yeast Schizosaccharomyces pombe (69)(70)(71)266), the human pathogen Candida albicans (79), the filamentous fungi Neurospora crassa (31,138) and Sordaria macrospora (176,205), the chestnut blight fungus Cryphonectria parasitica (282), the rice blast pathogen Magnathorpe grisea (242), the white blight pathogen Gibberella zeae (139,158), and the cellulase producer Hypocrea jecorina (238). For H. jecorina, the precursor is unusual, sharing commonalities with S. cerevisiae a-factor and ␣-factor precursors.…”
Section: Lipophilic Pheromones Are Common Among Fungimentioning
confidence: 99%
“…Genes of two classes of pheromones were identified recently from three heterothallic filamentous fungi, C. parasitica, M. grisea and Neurospora crassa, and from the homothallic fungus Sordaria macrospora (Zhang et al, 1998;Shen et al, 1999;Poggeler, 2000;Bobrowicz et al, 2002;Turina et al, 2003). The first complete set of pheromone precursor genes to be identified in a filamentous ascomycete was from C. parasitica (Zhang et al, 1998), and three pheromone precursor genes, Mf1/1, Mf2/1 and Mf2/2, have been reported to exist in both C. parasitica mating types (Zhang et al, 1998;Turina et al, 2003). The expression of the pheromone precursor genes is mating-type-specific; for example, Mf1/1 is expressed only by Mat-1 strains, and the genes display transcriptional suppression, characteristic of a virus-containing hypovirulent strain.…”
Section: Strainmentioning
confidence: 99%
“…The downregulation of pheromone gene expression owing to alterations in the expression of CpMK2, which belongs to a family of pheromone-responsive MAPKs, could imply that pheromone gene expression is dependent on the MAPK pathway, as in S. cerevisiae, and that a MAPK cascade similar to the S. cerevisiae FUS3/KSS1 MAPK pathway exists in C. parasitica. Based on the significant similarities in the structures and expression patterns of the pheromone precursor genes of C. parasitica and the ascomycetous yeasts, it is expected that the features of the mating system of yeasts are conserved in C. parasitica and that pheromone expression in C. parasitica is regulated by the mating-type locus, which encodes transcriptional regulators (Zhang et al, 1998;Shen et al, 1999). Therefore, the finding that disruption of CpMK2 results in inhibited pheromone gene expression could provide clues to intriguing connections between possible mating signals and a MAPK pathway in a phytopathogenic fungus.…”
Section: Strainmentioning
confidence: 99%